The impact of urbanization and institutions of higher education on Houston Texas’ Third Ward Community - AI Akpan (Journal of Applied Sciences and Environmental Management, 2009)
University towns are influenced by the features of urbanization and impact greatly on the health of the inhabitants. This paper evaluates the impacts of urbanization on the Third Ward communities that are located within Texas Southern University and the University of Houston. The paper further assesses how characteristics of the urban environment may have affected the population health. The historical background of the Third Ward Houston Texas is first reviewed to determine the extent to which urbanization and the presence of universities have impacted on the quality of life of the residents. The overall effects of urbanization are reviewed using all the available literature with broad emphasis on the physical, and social environments, and access to health and social services. Irrespective of the presence of universities and colleges, the surrounding neighborhood communities of the Third Ward Houston continue to face formidable historic challenges to improving public health and general quality of life. Although, urbanization has brought about reinvestment initiatives, changing demographics, and growth creating changes that offer new opportunities for improving health while requiring that health systems be adapted to residents' health needs, however, the communities remain stagnant and unique. Ultimately, the key factors affecting the quality of life in the Third Ward communities are the physical environment, the social environment, and access to health and social services. Overall, the neighborhood communities of the Third Ward do not seem to respond positively to developmental influence of the universities and colleges and are negatively impacted by urbanization. It is suggested that improvement in the Third Ward areas should require setting local, state, and national agendas for progress. Therefore, certain priorities must be put in place namely, development must reorient around the educational and population dynamics, including cultural diversity, and the growing numbers of elderly. @JASEM